Geoinformation modeling of pollution of the territorie with the main dose-forming radionuclides: retrospective, current state (on the example of the Gomel region) - Zhuravkov, Vladislav V.; Tsybulka, Mikalai M.; Lasuta, Gennady F.; Zhuravkov, Evgeniy V. (Journal of the Belarusian State University. Ecology, 2026)
Comprehensive geoinformation modeling of contamination of the territory of the Gomel region with the main dose-forming radionuclides has been performed online based on the integration of archived data from radiometric surveys, geological maps and field measurements. The paper implements methods of spatial interpolation, temporal trend analysis and forecasting based on physico-ecological models of radionuclide migration in soil and plant systems. Spatial interpolation methods were used to reconstruct continuous spatial distributions of radionuclide concentrations (131I, 132Te, 103Ru, 95Nb, 239Np, 99Mo, 106Ru, 140Ba, 141Ce, 144Ce, 95Zr, 137Cs, 90Sr, 238, 239, 240Pu) based on discrete point measurements: inverse weighted distance, kriging with external drift, triangulation Delaunay with linear interpolation. A retrospective analysis of the dynamics of contamination of the territory of the Gomel region with the main dose-forming radionuclides since 1986 has been carried out, stable zones with delayed degradation of activity have been identified, and a forecast of levels of contamination with radionuclides up to 2056 has been constructed. The results showed that 13⁷Cs remains the dominant dose-forming nuclide (more than 85% of the current effective dose), while its activity decreased by an average of 68-72% over 40 years. Forecast for 2056 It indicates a further decrease in activity to 15-25% of current values, however, areas with high pollution density will remain objects of increased radiation control. The resulting cartograms and models can be integrated into radiation monitoring and land-use planning systems.